2012 1st International Symposium on Physics and Technology of Sensors (ISPTS-1) 2012
DOI: 10.1109/ispts.2012.6260969
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically controlled flexible valve for flow manipulation in polymer microfluidic devices

Abstract: The paper describes design and fabrication of simple, magnetically actuated flexible polymer valve for flow manipulation in the microfluidic network. The valve is made up of a polymer composite. The CoFe 2 O 4 was embedded in PDMS (Polydimethylsiloxane) for making this polymer composite. The composites of different volume percentage loading of CoFe 2 O 4 were used and for each concentration valves of different thicknesses were fabricated, as thin rectangular membranes. This membrane was magnetized in the thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Both the chambers were sealed using a thin glass cover. PDMS-magnetic needle (Figure 2e) was fabricated 34 as detailed in the Supporting Information (page S-1).…”
Section: Methodsmentioning
confidence: 99%
“…Both the chambers were sealed using a thin glass cover. PDMS-magnetic needle (Figure 2e) was fabricated 34 as detailed in the Supporting Information (page S-1).…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of a small NdFeB magnet lying below the channel of interest, the metal bar is pulled downward simultaneously pushing the thin layer of PDMS down thereby closing the channel and stopping any flow of fluid. Furthermore, Bute et al [121] reported that the flow manipulation and proper operation of the valve depends on thickness and percentage load of magnetic material in the membrane as well as dimensions of channel, chamber and membrane with respect to the location of outlet channels, while Nakahara et al [122] reported the use of photosensitive polymer composites for the fabrication of magnetically driven microvalve arrays in a µTAS (µ-total analysis system)…”
Section: Polymer-based Electromagnetic Actuators For Micropumps and Microvalvesmentioning
confidence: 99%
“…In the presence of a small NdFeB magnet lying below the channel of interest, the metal bar is pulled downward simultaneously pushing the thin layer of PDMS down thereby closing the channel and stopping any flow of fluid. Furthermore, Bute et al [121] reported that the flow manipulation and proper operation of the valve depends on thickness and percentage load of magnetic material in the membrane as well as dimensions of channel, chamber and membrane with respect to the location of outlet channels, while Nakahara et al [122] reported the use of photosensitive polymer composites for the fabrication of magnetically driven microvalve arrays in a μTAS (μ-total analysis system)…”
Section: Polymer-based Electromagnetic Actuators For Micropumps and Microvalvesmentioning
confidence: 99%